Position and Responsibilities of a Substitute Notary for a Notary Who Has Died - Pratidina, Merry Fitri; Hafidz, Jawade (TABELLIUS: Journal of Law, 2024)
This study aims to understand and analyze the position and responsibility of a Substitute Notary towards a Notary who has died and its legal consequences. This type of research uses normative juridical and the analytical tools in this study are the theory of legal objectives and the theory of legal responsibility. The results of the research and discussion show that a substitute Notary is tasked with replacing or taking over all obligations of a notary who is taking leave within a specified period of time. A Substitute Notary has the same obligations and authorities as a regular Notary. This is in accordance with the provisions in Article 33 paragraph (2) of the Notary Law which stipulates that the provisions in Article 4, Article 15, Article 16 and Article 17 of the Notary Law apply and are also binding on Substitute Notaries, as long as it is not specified otherwise. Substitute Notaries have the same responsibility in carrying out their duties, in accordance with the provisions of Article 65 of the UUJN. As a result of the legal position and responsibility of the Substitute Notary towards the Notary who is replaced who dies, the heirs can propose that the Notary Holding the Protocol and the MPD appoint a Notary as the recipient of the protocol or the MPD appoints a Notary who receives the protocol for a period of 14 (fourteen) days from the end of the term of office of the Temporary Notary.